2013
DOI: 10.1155/2013/807346
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal Abscess as Initial Presentation of Squamous Cell Carcinoma

Abstract: We report a case of scrotal squamous cell carcinoma in a 67-year-old man that presented as a recurrent nonhealing scrotal abscess. Radical scrotectomy and bilateral simple orchiectomy were performed. A pudendal thigh flap was used for wound closure. To our knowledge, this is the first report of its use after radical surgery for scrotal cancer. The clinical features, staging, and treatment of scrotal squamous cell carcinoma are reviewed. In this report, we highlight the importance of including scrotal cancer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Over 83% (5/6) of patients who did undergo DRE demonstrated positive findings, including a palpable mass (4), purulent anal drainage (1), and pain out of proportion (1). This over 80% rate of positive findings on DRE is consistent with a study by the World Journal of Gastroenterology in 2015 which showed that preoperative DRE resulted in positive findings in 75% of FG with underlying rectal cancer and it highlights the importance of including a thorough anorectal examination in all patients with FG [ 1 , 3 , 15 - 17 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Over 83% (5/6) of patients who did undergo DRE demonstrated positive findings, including a palpable mass (4), purulent anal drainage (1), and pain out of proportion (1). This over 80% rate of positive findings on DRE is consistent with a study by the World Journal of Gastroenterology in 2015 which showed that preoperative DRE resulted in positive findings in 75% of FG with underlying rectal cancer and it highlights the importance of including a thorough anorectal examination in all patients with FG [ 1 , 3 , 15 - 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…Local procedures and chronic indwelling catheters increase the risk of infection. Chemotherapy as a treatment for a previously diagnosed unrelated cancer was seen in 15% (3/20) of the case reports [3][4][5][6][7].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient 2 presented with T4 N1 M1 disease and locally destructive mass as well as confirmed metastatic intraabdominal lymph node involvement. Both patients had delayed presentations to a health care professional, which is in keeping with the literature [8].…”
Section: Discussionsupporting
confidence: 85%